The answer is: [B]: 4 + y .
______________________
The rest of the answer choices given are all different ways to express, or are equivalents of, the number "4", multiplied by the variable, "y".
______________________
There are two ways to do this
Method 1:
Find (f-g)(x) first
(f-g)(x) = f(x) - g(x)
(f-g)(x) = (5x^2+3) - (-2x+4)
(f-g)(x) = 5x^2+3+2x-4
(f-g)(x) = 5x^2+2x-1
Then plug in x = -3
(f-g)(-3) = 5(-3)^2+2(-3)-1
(f-g)(-3) = 5(9)+2(-3)-1
(f-g)(-3) = 45-6-1
(f-g)(-3) = 39-1
(f-g)(-3) = 38
-----------------------------------------
Method 2:
Find f(-3)
f(x) = 5x^2+3
f(-3) = 5(-3)^2+3
f(-3) = 5(9)+3
f(-3) = 45+3
f(-3) = 48
Find g(-3)
g(x) = -2x+4
g(-3) = -2(-3)+4
g(-3) = 6+4
g(-3) = 10
Subtract the two results
(f-g)(-3) = f(-3) - g(-3)
(f-g)(-3) = 48 - 10
(f-g)(-3) = 38
-----------------------------------------
Whichever method you pick, the answer is: 38
The answer to your question is A
From sin(180-x) = sin(x)
sin(150) = sin(180-30) = sin(30)
sin(120) = sin(180-60) = sin(60)
from cos(360-x) = cos(x)
cos(300) = cos(360-60) = cos(60)
cos(210) = cos(360-150) = cos(150)
from cos(180-x) = -cos(x)
cos(210) = cos(150) = cos(180-30) = -cos(30)
No because the exact opposite of -3 would be 3.